(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the evolving landscape of youth empowerment and government policy in Uzbekistan. It highlights the significant contributions made by the country’s youthful population across various sectors, including entrepreneurship, arts and culture, social activism, and education. The article underscores the importance of harnessing the potential of Uzbekistan’s youth demographic and emphasizes the role of government policies in facilitating their development and participation in nation-building. The article acknowledges Uzbekistan’s predominantly young population and discusses how this demographic presents both opportunities and challenges for the country’s socio-economic development. It identifies specific achievements of Uzbekistan’s youth, showcasing their endeavors in entrepreneurship, arts, social activism, and education, demonstrating their impact on the country’s cultural and economic landscape. The article explores the evolution of Uzbekistan’s youth policy, emphasizing key areas such as education, employment, civic engagement, and health, underscoring the government’s commitment to supporting youth development. It concludes by highlighting the potential of Uzbekistan’s youth in shaping the nation’s future and stresses the importance of continued investment in youth-oriented policies and initiatives to realize sustainable development goals. Overall, this annotation provides a concise summary of the article’s main themes and highlights its relevance in understanding the role of youth empowerment and policy frameworks in the context of Uzbekistan’s socio-economic landscape.